Savonius wind turbine blade selection based on computational fluid dynamics - Achmad Fauzan Hery Soegiharto; Andinusa Rahmandika; Ahmad Nur Sidiq (JTTM : Jurnal Terapan Teknik Mesin, 2024)
The Savonius vertical axis wind turbine is widely used because of its simple design and efficiency at low wind speeds. The next development is the mini multi-blade Savonius helical wind turbine. At this miniature size, the performance of a mini multi-blade helical Savonius turbine due to variations in the number of blades and its impact on the energy produced has not been investigated in depth. Therefore, adjustments to the size and number of blades need to be made to optimize the performance of this turbine. The research aims to obtain the performance of the Savonius type S wind turbine with 3 blades and 4 blades using the CFD (Computational Fluid Dynamics) method. The main dimensions of the simulation model are the shaft diameter of 0.008 m, the outer diameter of 0.24 m, the height of 0.4 m, and the number of blades 3 and 4. The inner diameter of the 3-blade turbine is 0.21 m while the inner diameter of the 4-blade turbine is also 0.21 m. Both turbine models are subjected to wind speeds of 4 m/s, 5 m/s, and 6 m/s. Based on the simulation results, a turbine with 4 blades has more optimal performance compared to the 3-blade type. At a wind speed of 6 m/s, the 4-blade Savonius helical turbine produces a rotation of 498,215 rpm and a maximum power of 6,129 watts. Meanwhile, the Savonius turbine with 3 blades at a wind speed of 6 m/s produces a rotation of 545,655 rpm and a maximum power of 4,390 watts. This difference in performance shows the importance of adjusting the number of blades in wind turbine design to achieve optimal efficiency. This research provides useful insights for the further development of mini helical Savonius wind turbines in various wind conditions